ANALISIS REVALUASI ASET TETAP DALAM PENETAPAN PAJAK PENGHASILAN PADA PT. BANK SULUTGO - Polopadang, Stefian; Tinangon, Jantje J.; Elim, Inggriani (Universitas Sam Ratulangi, 2018)
Tax is the one of the outcome of a company without making any profit directly, therefore in paying tax a company do the effort so the payment becomes a bit less without breaking the rules in tax which is prevail. One of the way to minimize the tax is using one of the accounting policies, revaluation of fixed assets. The formulation of the problem of this research is the role of revaluation of fixed assets in determining incoming tax. The kind of this research which is used, is qualitative descriptive with the theory and using the object of the research in PT. BANK SULUTGO. According to the analysis and research which is suit with regulation 36 Taxation on Income Tax Year 2008 and Decree of the Minister of Finance 486/KMK/2002 that by applying the revaluation the fair market value of the acquired fixed assets newly, where the fair market value of fixed assets can be seen the value of revaluation of fixed assets, then the amount of final income tax imposed at 6%Â based on the book 2016 accrording to Minister of Finance Regilation 191 Year 2015.Keywords: Revaluation, Fixed Asset, Income Tax